Theachers' Roles and Pedagogical Strategies in the Integration of 21st Century Skills in Educational Institutions - Musafah, Aziz; Mubarok, Khotimul; ‘Adani, M. Zaki (UM Purwokerto Press, 2025)
Global transformation and rapid technological advancement have compelled the world of education to adapt to the demands of 21st-century skills. In this context, teachers play a crucial role as learning facilitators who must be able to implement strategies that are relevant to both current and future needs. The objective of this study is to systematically examine the role of teachers and instructional strategies in supporting the implementation of 21st-century skills in educational institutions. This research adopts a systematic literature review method by analyzing several scholarly articles to obtain structured data on teaching strategies for applying 21st-century skills. The findings indicate that teachers have a central role in designing and implementing learning processes that foster critical thinking, communication, collaboration, and creativity (the 4C). Effective instructional strategies in this context include project-based learning, problem-based learning, and the integration of digital technology into teaching and learning activities. Teachers who successfully adopt these innovative strategies have been shown to enhance student engagement and promote collaborative and reflective learning environments. However, many teachers still face challenges related to training, understanding the concept of 21st-century skills, and limited supporting facilities in educational institutions. Therefore, it is essential for educational institutions and governments to provide ongoing professional development programs for teachers, along with adequate infrastructure and resources. These efforts are necessary to ensure the optimal and equitable implementation of 21st-century skills across all levels of education.